Development, function, and clinical significance of plasmacytoid dendritic cells in chronic myeloid leukemia - Inselmann, Sabrina; Wang, Ying; Saußele, Susanne (Cancer research, 2018)
Plasmacytoid dendritic cells (pDC) are the main producers of a key T-cell-stimulatory cytokine, IFNα, and critical regulators of antiviral immunity. Chronic myeloid leukemia (CML) is caused by BCR-ABL, which is an oncogenic tyrosine kinase that can be effectively inhibited with ABL-selective tyrosine kinase inhibitors (TKI). BCR-ABL-induced suppression of the transcription factor interferon regulatory factor 8 was previously proposed to block pDC development and compromise immune surveillance in CML. Here, we demonstrate that pDCs in newly diagnosed CML (CML-pDC) develop quantitatively normal and are frequently positive for the costimulatory antigen CD86. They originate from low-level BCR-ABL-expressing precursors. CML-pDCs also retain their competence to maturate and to secrete IFN. RNA sequencing reveals a strong inflammatory gene expression signature in CML-pDCs. Patients with high CML-pDC counts at diagnosis achieve inferior rates of deep molecular remission (MR) under nilotinib, unless nilotinib therapy is combined with IFN, which strongly suppresses circulating pDC counts. Although most pDCs are BCR-ABL-negative in MR, a substantial proportion of BCR-ABL+ CML-pDCs persists under TKI treatment. This could be of relevance, because CML-pDCs elicit CD8+ T cells, which protect wild-type mice from CML. Together, pDCs are identified as novel functional DC population in CML, regulating antileukemic immunity and treatment outcome in CML. - Significance: CML-pDC originates from low-level BCR-ABL expressing stem cells into a functional immunogenic DC-population regulating antileukemic immunity and treatment outcome in CML. Cancer Res; 78(21); 6223-34. ©2018 AACR.
Gesehen am 18.02.2020